PENANAMAN SIKAP SOSIAL PADA PEMBELAJARAN TEMATIK MUATAN ILMU PENGETAHUAN SOSIAL KELAS IV SD NEGERI GEDONGKUNING KOTAGEDE - Dyah Ayu Fitriyana; Trisharsiwi Trisharsiwi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2018)
The aim of the research is to get in idea about inculcation of of in thematic learning containing social attitudes to four grade students of Gedongkuning State Elementary School. Tools used in this research consist of researcher as main instrument, interview paper, observation paper, and documentation. Data analysis technique consist of data collection, data reduction, data display, and conclusion. The result of this research shows that the inculcation social attitudes are mutual respect, respectcare for others. School efforts in inculcating social attitudes include providing examples of good behavior for students, forming groups in learning, remind the student about social study. Student interaction four grade students enough. Supporting factors of social studies inculte social attitudes are coorperation parents, teacher and community. The obstacle factors inculcation social attitudes are student association not monitore continue the teacher, social attitudes student low awareness.have behavior from the home. The result of inculcation social attitudes to four grade students of Gedongkuning State Elementary Schoolis example good behavior by teacher and other people, give the understanding and remind about social stidies to student.